An Element‐Substituted Cyclobutadiene Exhibiting High‐Energy Blue Phosphorescence. (7th July 2021) - Shoji, Yoshiaki; Ikabata, Yasuhiro; Ryzhii, Ivan; Ayub, Rabia; El Bakouri, Ouissam; Sato, Taiga; Wang, Qi; Miura, Tomoaki; Karunathilaka, Buddhika S. B.; Tsuchiya, Youichi; Adachi, Chihaya; Ottosson, Henrik; et al.
Abstract: 1, 3, 2, 4‐Diazadiboretidine, an isoelectronic heteroanalogue of cyclobutadiene, is an interesting chemical species in terms of comparison with the carbon system, whereas its properties have never been investigated experimentally. According to Baird's rule, Hückel antiaromatic cyclobutadiene acquires aromaticity in the lowest triplet state. Here we report experimental and theoretical studies on the ground‐ and excited‐state antiaromaticity/aromaticity as well as the photophysical properties of an isolable 1, 3, 2, 4‐diazadiboretidine derivative. The crystal structure of the diazadiboretidine derivative revealed that the B2 N2 ring adopts a planar rhombic geometry in the ground state. Yet, theoretical calculations showed that the B2 N2 ring turns to a square geometry with a nonaromatic character in the lowest triplet state. Notably, the diazadiboretidine derivative has the lowest singlet and triplet states lying at close energy levels and displays blue phosphorescence. Abstract : We report the ground‐ and excited‐state aromaticity and photophysical properties of a planar cyclic 4π system, based on studies on a diazadiboretidine derivative, an isoelectronic heterocyclic analogue of cyclobutadiene. Diazadiboretidine, despite having the lowest singlet and triplet states lying at close energy levels, displays blue phosphorescence, rather than thermally activated delayed fluorescence.